1993
DOI: 10.1007/bf00919287
|View full text |Cite
|
Sign up to set email alerts
|

Cellular fibronectin on intraocular lenses explanted from patients

Abstract: We investigated the origin of fibronectin (FN) on five posterior and four anterior chamber explanted intraocular lenses (IOLs) using immunohistochemical methods. Cellular deposits (assumed to be macrophages) and fibrous or membrane-like proteinaceous deposits on the IOLs showed immunoreactivity to an antibody against cellular FN. These proteinaceous deposits were believed to be products of the cells that adhered to the IOLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The mean collagen produced by proliferating lens epithelial cells around the IOL may also be altered to types I and III, as the condition for proliferation of cells on IOL optics resembles that of the cell culture, i.e., the growth of cells on a plastic material. We previously detected immunohistochemically the deposition of collagen types I, III and IV and of cellular fibronectin, accompanied by adhesion of macrophages foreignbody giant cells and presumed lens epithelial cells on PMMA IOLs that were explanted from patients during vitreous surgery performed for PVR or PDR (Saika et al, 1992(Saika et al, , 1993. The growth factor components found in the intraocular fluid were elevated under such conditions (Connor et al, 1989 ;GonzalezAvila et al, 1995).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The mean collagen produced by proliferating lens epithelial cells around the IOL may also be altered to types I and III, as the condition for proliferation of cells on IOL optics resembles that of the cell culture, i.e., the growth of cells on a plastic material. We previously detected immunohistochemically the deposition of collagen types I, III and IV and of cellular fibronectin, accompanied by adhesion of macrophages foreignbody giant cells and presumed lens epithelial cells on PMMA IOLs that were explanted from patients during vitreous surgery performed for PVR or PDR (Saika et al, 1992(Saika et al, , 1993. The growth factor components found in the intraocular fluid were elevated under such conditions (Connor et al, 1989 ;GonzalezAvila et al, 1995).…”
Section: Discussionmentioning
confidence: 89%
“…Ishibashi and coworkers (1994) detected collagen types I and III, the major components of collagenous connective tissue, in opacifications of human posterior capsules by immunoelectron microscopy. We have detected deposition of various extracellular matrix components, including collagen types I and IV and cellular fibronectin, on the surfaces of IOLs explanted from patients or rabbits (Saika et al, 1992(Saika et al, , 1993(Saika et al, , 1997a(Saika et al, , 1997b. Therefore, we believe that these matrix proteins are the components accumulated on the capsules.…”
Section: Introductionmentioning
confidence: 92%
“…Different fibronectin concentrations have been measured in aqueous humor of patients before glaucoma or cataract surgery, indicating a disruption of the blood-aqueous barrier in glaucomatous eyes [16]. Immunohistochemical studies revealed proteinacous deposits containing fibronectin within the capsular bag and on the surfaces of explanted IOLs [12,13]. The inflammatory response after cataract surgery could conceivably result in exposure of fibronectin of plasma origin to the aqueous humor, the LECs, and the posterior capsule.…”
Section: Discussionmentioning
confidence: 98%
“…Since fibronectin is one major ECM component responsible for cell differentiation and proliferation, it has been considered of importance in the development of secondary cataract. Fibronectin has been demonstrated in human aqueous humor and on deposits found on explanted IOLs and capsular bags [12,13,16], although it is yet unclear how fibronectin gains access to intraocular structures. More studies are necessary to determine the mechanism by which different compositions of polymers modulate the proliferation-stimulating interaction between the adsorbed fibronectin molecule and adherent cells.…”
Section: Discussionmentioning
confidence: 99%
“…In previous immunohistochemical studies, we found that proteinaceous deposits on the surfaces of explanted polymethylmethacrylate (PMMA), IOLs contained collagen types I and IV, cellular fibronectin, and vitronectin [26,28,29]. Deposits immunoreactive for collagen types I, III, and IV and cellular fibronectin were also observed on PMMA and silicone IOLs that were experimentally implanted in rabbit eyes [32,33].…”
Section: Introductionmentioning
confidence: 82%